Influence of ECAP on the structure and properties of Ti18Zr15Nb and Ti10Mo8Nb6Zr alloys for medical application - Churakova, A. A.; Gunderov, D. V.; Raab, G. I.; Prokoshkin, S. D.; Sheremetyev, V. A.; Filho, Paulo N Lisboa [UNESP]; Pedro, João [UNESP]; Claro, Ana Paula Rosifini Alves [UNESP] (IOP Publishing, 2021)
Studies of the influence of ECAP on the structure and properties of the metastable ß-Ti alloys Ti18Zr15Nb and Ti10Mo8Nb6Zr have been carried out. The XRD data shows that the BCC ß is the main phase in the initial alloys and alloys after ECAP. As a result of ECAP, the strength and yield stress of the alloys increases significantly due to the refinement of the structure. After ECAP, UTS and YS of the Ti10Mb8Nb8Zr alloy increase more noticeably than the Ti18Zr15Nb alloy, but after 7 ECAP cycles according to the regimes used (n = 6 T 250 °C + n = 1 350 °C), the Ti10Mb8Nb8Zr alloy becomes brittle. The increment in the yield point of the Ti18Zr15Nb alloy after ECAP processing together with the preservation of the ß-state, allows one to expect an increase in the functional properties of the alloy.